The Systematic Theory on Geomorphology with Emphasis on Glacial Areas (Case Study, Oshtorankuh region) - Ebrahim Moghimi; Mohamad Fathollahzadeh (تحقیقات کاربردی علوم جغرافیایی)
System is a set of interconnected components that are systematically interconnected, influenced by one another, interacting with one another, acting as a whole, and being purposeful. A systematic approach is a perspective that allows us to identify the forces and variables that have a significant impact on the environment outside and within a complex and to understand their function and position in the complex. In general, the interplay of form and process in landforms is based on systematic reviews and analysis by researchers and the residual effects of these changes.  In this study, the study of glacial geomorphic systems with regard to systematic approach and the interaction between form and process in glaciers of Oshtorankuh is investigated. Geomorphometric analysis of the glacier cirques of the Oshtorankuh region shows that these landforms, unlike the usual glacier cirques, have been expanded more horizontally and superficially than were investigated in depth direction to justify the genesis and lithology of the area. It is often calcareous and carbonate and the carbonate nature of the environment activates the dissolution process in the environment. Therefore, in this glacier system, the dissolution factor is more effective than other active elements.